Precise Spatial Prediction of Rice Seedlings From Large-Scale Airborne Remote Sensing Data Using Optimized Li-YOLOv9 - Jayakrishnan Anandakrishnan; Arun Kumar Sangaiah; Hendri Darmawan; Nguyen Khanh Son; Yi-Bing Lin; Mohammed J. F. Alenazi (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Rice is pivotal in global food security and Rice seeding detection in precision agriculture is essential for optimizing crop productivity and efficient resource use. Currently, the spatial distribution and detection of rice seeding are manually done, which is time-consuming. As technology advances, the rapid progress in precision agriculture calls for innovative solutions like lightweight edge-computing vision models for unmanned aerial vehicle (UAV) intelligence. However, the limited computational capabilities of UAVs make it challenging to deploy complex object detection models onboard. This article proposes Li-YOLOv9, an efficient, lightweight, and precise object detection model for detection of rice seedlings from large-scale UAV remote sensing data. The proposed Li-YOLOv9 includes a 3-D feature adaptation module, convolutional block attention modules, coordinate attention module, and deepwise point convolution modules, which offer significant advantages over the original YOLOv9. The compact Li-YOLOv9 with approximately 9 million parameters is significantly lighter than the original YOLOv9 with 60 million parameters, making it ideal for resource-efficient onboard intelligence. Li-YOLOv9 is tested and validated against a real UAV rice seedling dataset. It showcases exceptional detection capabilities, achieving impressive metrics across various performance indicators, including a mean average precision of 99.60%, an $F1$ -score of 96.95%, an average recall of 96.70%, and an average precision of 97.20% in comparison to the state-of-the-art. Li-YOLOv9 is highly efficient and ideal for UAV deployment for real-time detection of rice seedlings from large-scale remote sensing data.